ChemInform Abstract: Study and Application of Noncatalyzed Photoinduced Conjugation of Azides and Cycloocta‐1, 2, 3‐selenadiazoles. Issue 31 (14th July 2016) - Jedinakova, P.; Sebej, P.; Slanina, T.; Klan, P.; Hlavac, J.
Abstract: 1, 2, 3‐Triazoles are prepared by cycloaddition of azides with cyclooctyne in situ generated by photolysis of cyclooctaselenadiazole (I).